Clinical and radiographic assessment of peri-implant tissue changes using two different implant connections with immediate implant placement and loading.: Randomised controlled clinical trial - Mobarek, Salma; Kamal Abdel Gaber, Hala; Samy Zaki, Mohamed; Bissar, Mohamed (Brazilian Journal of Implantology and Health Sciences, 2022)
Aim: Radiographic assessment of dimensional changes of peri implant tissues in immediately placed implants with non-functional loading in maxillary esthetic zone with Internal Hex (IH) and Conical Tapered (CT) connections Materials and Methods: 20 immediately placed implant with immediate loading were inserted in the maxillary esthetic zone, patients meeting the inclusion criteria were allocated into one of the two groups: Internal Hex or Conical tapered connection. Results: Pink Esthetic Scores(PES) of the CT connection showed significantly higher values than IH. It was shown that the IH group showed statistically significant higher mean value than the CT connection in the values of crestal bone loss using CBCT. Conclusion: CT connection has proved to result in better clinical, radiographic and volumetric outcomes than IH.